Comparative study of floral characteristics in the component lines of hybrid rice (Oryza sativa L.) (Bangladesh Journal of Botany, 2014)
Significant variations were obtained among the component lines for most of the floral traits. BRRI9A exhibited superiority for angle of open florets, stigma length and breadth, anther breadth, filament length, style length and panicle exertion rate while its corresponding maintainer lines BRRI9B showed superiority for duration of open florets, stigma length and breadth, anther breadth and filament length. This indicated BRRI9A and its corresponding maintainer line BRRI9B possessed very good floral traits that influence out crossing. Among the restorer lines BR168R showed superiority for duration of open florets, angle of open florets, duration of bloomed florets/panicle, stigma length, anther length and number of pollen/microscopic focus. This suggested BR168R could be used as promising restorer line with BRRI9A for hybrid seed production in local condition.DOI: http://dx.doi.org/10.3329/bjb.v43i1.19739 Bangladesh J. Bot. 43(1): 1-8, 2014 (June)